Edukasi CABG Berbasis Android dalam Meningkatkan Kualitas Hidup Pasien Post Operasi CABG - Agritubella, Syafrisar Meri; Yuliyana, Rian; Masnun, Masnun; Ardenny, Ardenny (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effectiveness of Android-based CABG education in improving the quality of life of post-CABG surgery patients. The research method used is experimental research. Measurement of patient quality of life using the Short from Survey 36 (SF36) questionnaire. The data that has been obtained will be categorized based on a scale of 0-100. The results showed that the average quality of life of patients in the experimental group was in the good category (mean = 64.99), and in the control group was also in the good category (mean = 62.28). Based on the research results, both groups showed good categories. Still, the average quality of life score for the experimental group was greater than that of the intervention group, so the provision of Android-based CABG education had a positive effect on the quality of life of post-CABG surgery patients. In conclusion, Android-based CABG education improves the quality of life of post-CABG surgery patients compared to conventional education. Keywords: Android, CABG, Education, Quality of Life, Post Surgery.